Cultivation vs the ‘omics’ approach for microbial bioprospecting in the 21st century: coastal environment in Malaysia - Mohd Omar, Suhaila (Noor Publishing, 2020)
The coastal environment is the habitat of diverse functionally important marine microorganisms. Among the valuable characteristics of the microorganisms for bioprospecting studies are not limited to tolerant toward rapid and repeated fluctuations in temperature, sunlight, salinity, wave action, ultraviolet radiation, and periods of drought. On the other hand, microorganisms that are living the epiphytic, epibiotic, and symbiotic lifestyles produce specific toxins, signaling molecules, and other secondary metabolites due to their defence and signaling mechanism. The traditional and innovative cultivation method is still relevant in bioprospecting studies while the ‘omics’ approaches offer an extensive gateway towards microorganism diversity and function. Therefore, this minireview focus on the challenges, strategies and the success of microbial bioprospecting studies in the context of Malaysia coastal environment via cultivation and ‘omics’ approach.